Auto-declaração de cor e/ou raça entre alunos(as) paulistanos(as) do Ensino Fundamental e Médio: um estudo exploratório - Rocha, Edmar José da (2005)
This assignment, which joins the contemporaries studies on racial relations in Brazil, focuses in the subject of the racial classification and explores the auto-classification of colour and/or race between children and adolescents, pupils of public schools of the city of São Paulo. When giving voice to children and adolescents, I try to associate a political objective to the knowledge plan, gathering the new paradigms of the infancy studies. In this context, it is understood that children and adolescents are social actors and therefore, they have the right to express their racial background. Appraising race as a social construction, it presents and it argues the contemporary bibliography on racial classification, evidencing two gaps: one with respect to the methodological aspects, in which, It has not been questioned the understanding or agreement of the population with respect to the terms of colour and race; the other, relative to the voice of children and adolescents. The Research work consisted of the collection and analysis of answers of 238 children and adolescents, of both genders, organized in parallel groups, the three types of questionnaires in which varied the use of the terms colour, race and colour/race. In the ethical plan of this research, it was requested the children and to the adolescents an Informing assent term after the explanation of the research. The closed questions had been tabulated and the opened ones had previously passed for a process of content analysis aiming at to the apprehension of the concepts of colour and race expressed by the children and adolescents. It was observed that inquired children and adolescents express in consistent way its conceptualizations, and that, despite expressing a lesser number of racial terms then adults investigated in other research, they evidence a standard and equivalent answers. It is concluded suggesting that, In spite of the silence that impregnates the racial relations in the school, the children and the adolescents possess the ability to express, themselves their racial background